Developing the basics of pavement management system in Besiktas district and evaluation of the selected sections - Kirbas, Ufuk; Gursoy, Mustafa (ACADEMIC JOURNALS, 2010)
Pavement management is in a broader sense, a working program that involves all the procedures of planning, programming, designing, building, maintaining, and rehabilitation. Pavement management concept is first introduced in the 1960's to ensure the best use of existing resources. Today many corporations in USA use managements systems either developed by themselves or modified to fit their climate, traffic, land, equipment, corporate structure and budget constraints. A pavement management system (PMS) arranges tools and methods to be used for determining the best maintenance schedule for the decision makers in a given period. A good pavement management is an integrated system which makes it necessary to think in a systematic and organized way, besides, it ensures that, necessary work is performed on daily basis. In this study, infrastructure distress data which is compatible with the distress identification manual published by American Society for Testing and Materials in 1999 is collected from 20 sections selected from the arterial road network in Besiktas district of Istanbul. The reasons for formation of distress types in the determined network are studied under the headings like axle load, climate and other (material characteristics), and distress evaluations throughout the whole network and each section are carried out.
Keywords: Pavement management system; paver system; pavement condition index (PCI); distress types; Science & Technology - Other Topics